A varied presentation of brown rice as a substitute for white rice. Issue 4 (July 2021) - Wijaya, Hengki; Rauf, Rusdiaman; Abdullah, N; Dirpan, A
Abstract: White rice is in great demand by Indonesians. However, in terms of nutrition and health impacts, brown rice is superior. The texture of brown rice is complex, and the taste is bland, so it is necessary to vary the presentation of brown rice and side dishes. In addition to the cooking method, brown rice is essential to maintain the nutritional value and give brown rice a softer texture. Organoleptic test method to see the texture and taste of brown rice. Literature review to find relevant research results with cooking methods and nutritional value.